Major hazard control: The Malaysian experience - Shaluf, Ibrahim M.; Ahmadun, Fakharu'l-Razi (Emerald Group Publishing, 2003)
Malaysia plans to be a fully developed and industrialized country by year 2020. Malaysia has achieved good progress in the industrial sector. The industrial sector is operating plants and factories using and storing hazardous substances in quantities exceeding the threshold quantities. The plants that are dealing with hazardous substances exceeding the threshold quantity are classified as major hazard installations (MHIs). Some MHIs are located in heavily populated areas. Experience shows that MHIs pose a risk to the workers and the neighbors of the plants. Malaysia has taken the preventive measures to protect the workers and the public. The preventive measures have been taken through establishment of authorities to set major hazard control regulations, enforcing the regulations, assessing the safety reports and emergency plans, conducting audits and accident investigations. This paper reviews, in brief, the international regulations and guidelines of major hazard control. The paper also reviews the Malaysian experience of major hazard control. © Emerald Group Publishing Limited.